PENGGUNAAN MODEL PEMBELAJARAN MAKE A MATCH PADA MATERI OPERASI HITUNG BILANGAN BULAT - Isnadayanti Isnadayanti; Andy Sapta (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: This research was conducted on grade VI students of Al Washliyah Elementary School Cab XII Sei Kepayang with the aim of improving student learning outcomes through the implementation of the learning process that applies the Make a Match type cooperative learning model on whole number counting operation material in grade VI of Al Washliyah Elementary School Cab XII Sei Kepayang. The type of research is Classroom Action Research which is conducted in two cycles. The data obtained in this study are student learning outcomes taken from giving learning outcomes test questions at the end of each cycle and observation sheets in each cycle. The results of the research in cycle I showed a percentage of classical completeness of 55% with eleven students who reached the KKM. While the research results in cycle II showed the percentage of classical completeness of 87.7% with eighteen students who reached the KKM. From this study it was concluded that by applying the cooperative learning model of the make a match type, the learning outcomes of grade VI students of Al Washliyah Elementary School Cab XII Sei Kepayang in the 2023/2024 academic year on the material of counting operations of whole numbers.Keywords: integers, Make a Match, number operations.Abstrak: Penelitian ini dilaksanakan pada siswa kelas VI SD Al Washliyah Cab XII Sei Kepayang bertujuan guna mengingkatkan hasil belajar siswa melalui pelaksanaan proses pembelajaran yang menerapkan model pembelajaran kooperatif tipe Make a Match pada materi operasi hitung bilangan bulat kelas VI SD Al Washliyah Cab XII Sei Kepayang. Adapun jenis penelitian ini adalah Penelitian Tindakan Kelas yang dilaksanakan dalam dua siklus. Data yang diperoleh dalam penelitian ini adalah hasil belajar siswa yang diambil dari pemberian soal tes hasil belajar pada akhir setiap siklus dan lembar observasi pada setiap siklus. Hasil penelitian pada siklus I menunjukkan persentase ketuntasan klasikal 55% dengan sebelas siswa yang mencapai KKM. Sedangkan hasil penelitian pada siklus II menunjukkan persentase ketuntasan klasikal 87,7% dengan delapan belas siswa yang mencapai KKM. Dari penelitian ini disimpulkan bahwa dengan diterapkan model pembelajaran kooperatif tipe make a match maka hasil belajar siswa kelas VI SD Al Washliyah Cab XII Sei Kepayang tahun pelajaran 2023/2024 pada materi operasi hitung bilangan bulat.Kata kunci: bilangan bulat, Make a Match, oprasi bilangan.